Feminist analysis of the novel Kretek Girl by Ratih Kumala - Iin Nuryati; Herwan; Ahmad Supena (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Babunnajah Pandeglang, 2025)
This study aims to describe the intrinsic elements, pro-feminist figures, counter-feminist figures, and stereotypes of women contained in the novel Gadis Kretek by Ratih Kumala. The theory used is Sugihastuti and Suharto's theory on feminist literary criticism. The research method used is a qualitative research method. The approach used is a feminist literary criticism approach in the form of reading as a woman. The technique used is the content study technique. The data sources used are primary data sources and secondary data sources. The research data used is qualitative data such as words, phrases, and sentences contained in the novel Gadis Kretek by Ratih Kumala. The data is then classified according to the data related to intrinsic elements and feminist literary criticism. Related to the analysis that the researcher has done, the research results are obtained, namely; (1) Intrinsic elements, (2) Pro-feminist figures are not only carried out by female characters, but there are male characters who are pro-feminists such as; Scribes, Idroes Moeria, Soedjagad, Dasiyah, Rukayah, Roemaisa, (3) Counterfeminist figures are not only carried out by male figures, but there are female figures who are involved in counterfeminist figures, such as; Lebas, Soeraja, Purwanti, (4) Stereotypes of women are carried out by pro-feminist figures as well as counterfeminist figures, such as; Lebas, Tegar, Idroes Moeria, Soeraja, Rukayah, Narrator.